Uji Efektivitas Khitosan terhadap Daya Awet Ikan Nila (Oreochromis niloticus) - Rina Sugiarti Dwi Gita; Hepta Bungsu Agung Jayawardana; Ahmad Afandi (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2021)
This study aims to determine the effect of the application of chitosan on fresh tilapia (Oreochromis niloticus) products as a natural preservative that can maintain the condition of fish with a longer shelf life. The method used in this study was experimental with three treatments, namely control treatment, 1% chitosan coating, and 1.5% chitosan coating. Data analysis was carried out through organoleptic tests with four parameters: color, aroma, texture, and taste of the tested tilapia. Observations were made for three consecutive days. The results showed that tilapia with 1.5% chitosan coating had better organoleptic parameter values than the other two test treatments. In conclusion, 1.5% of chitosan maintained the quality of tilapia with a longer shelf life. Keywords: Durability, Tilapia, Chitosan, Organoleptic